Delayed Ischemic Neurological Deficit after Uneventful Elective Clipping of Unruptured Intracranial Aneurysms - Vachata, Petr; Lodin, Jan; Hejčl, Aleš; Cihlář, Filip; Sameš, Martin (Brain sciences, 2020)
Cerebral vasospasm and subsequent delayed ischemic neurological deficit is a typical sequela of acute subarachnoid hemorrhage after aneurysm rupture. The occurrence of vasospasms after uncomplicated surgery of an unruptured aneurysm without history of suspected rupture is extremely rare. The pathogenesis and severity of cerebral vasospasms is typically correlated with the amount of blood breakdown products extravasated during subarachnoid hemorrhage. In rare cases, where vasospasms occur after unruptured aneurysm surgery, the pathogenesis is most likely multifactorial and unclear. We present two cases of vasospasms following uncomplicated clipping of middle cerebral artery (MCA) aneurysms and a review of literature. Early diagnosis and therapy of this rare complication are necessary to achieve optimal clinical outcomes.
Keywords: unruptured intracranial aneurysm; delayed ischemic neurological deficit; vasospasm